2020
DOI: 10.1038/s41598-020-60126-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the delta neutrophil index in pediatric cardiac arrest

Abstract: The delta neutrophil index (DNI), which reflects the ratio of circulating immature neutrophils, has been reported to be highly predictive of mortality in systemic inflammation. We investigated the prognostic significance of DNI value for early mortality and neurologic outcomes after pediatric cardiac arrest (CA). We retrospectively analyzed the data of eligible patients (<19 years in age). Among 85 patients, 55 subjects (64.7%) survived and 36 (42.4%) showed good outcomes at 30 days after CA. Cox regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…In previous studies, low DNI has been associated with increased survival to discharge [6,25]. In the present study, the DNI during initial ACLS was lower in the survival to discharge group than in the short-term mortality group, and the survival to discharge group had a lower DNI than the nonsurvival to discharge group.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In previous studies, low DNI has been associated with increased survival to discharge [6,25]. In the present study, the DNI during initial ACLS was lower in the survival to discharge group than in the short-term mortality group, and the survival to discharge group had a lower DNI than the nonsurvival to discharge group.…”
Section: Discussionsupporting
confidence: 60%
“…In one study, the risk of death in patients with in-hospital cardiac arrest (IHCA) increased when the cut-off value of NLR was higher than 4.5 [ 24 ]. In another study, DNI values higher than 3.3% at 24 hours significantly predicted 30-day mortality in patients with pediatric cardiac arrest [ 25 ]. In a serial follow-up of patients with OHCA, DNI at 3 days could be used to assess mortality and neurological outcomes [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…In children with ROSC from OHCA and IHCA, blood pressure monitoring and DNI can be considered to predict survival to discharge rates and short-term survival rates. 84,85 Furthermore, EEG monitoring to detect seizures and biochemical marker tests including blood NSE, S100 proteins, DNI, and diffusion-weighted magnetic resonance imaging can be considered to predict the neurological prognosis. 84,[86][87][88][89] A singlecenter retrospective observational study that targeted pediatric patients with OHCA showed that lactate level, Glasgow coma scale score, and the response to the pupillary light reflex test (which was conducted before initiating TTM immediately after ROSC) were factors that were significantly associated with the 6-month neurological prognosis.…”
Section: Predictors Of Outcomesmentioning
confidence: 99%